THE IMPACT OF CORPORATE GOVERNANCE ON FIRM FINANCIAL PERFORMANCE - A STUDY ON UK LISTED FIRMS - HARIHARAN, VARUN (2020)
The main aim of listed firms is to establish good corporate governance measures along with increasing the financial performance of the firms in the process. One of the major concerns faced by organisations is the separation of ownership and control. To reduce conflicts of intertest between managers and shareholders and increase financial performance, the board of directors play a crucial role. This research study has discussed the impact of corporate governance measures on firm financial performance in the case of UK listed retail firms.